2016
DOI: 10.1002/hed.24420
|View full text |Cite
|
Sign up to set email alerts
|

Effect of actionable somatic mutations on racial/ethnic disparities in head and neck cancer prognosis

Abstract: We have provided the proof-of-principal data to link racial/ethnic-specific somatic mutations and HNSCC prognosis and pave the way for precision medicine to overcome HNSCC survival disparities. © 2016 Wiley Periodicals, Inc. Head Neck 38:1234-1241, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…One caveat of our analysis is that this inference applies to a population as though our data were a representative sample of the population. HPV infection prevalence varies with socioeconomic factors [54], racial disparities [35, 55] and genetic polymorphisms [56, 57] associated with outcomes in head and neck cancer so greater attention to representative sampling would provide more precise estimates of the frequencies of mutations within populations [58] and the net realized selection intensities in each population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One caveat of our analysis is that this inference applies to a population as though our data were a representative sample of the population. HPV infection prevalence varies with socioeconomic factors [54], racial disparities [35, 55] and genetic polymorphisms [56, 57] associated with outcomes in head and neck cancer so greater attention to representative sampling would provide more precise estimates of the frequencies of mutations within populations [58] and the net realized selection intensities in each population.…”
Section: Discussionmentioning
confidence: 99%
“…Identification of targets via prevalence of substitutions assures that the altered gene will be relevant for the affected population, but gives little characterization of the efficacy of targeting the altered gene product at the level of the individual patient. In contrast, quantification of the effects that mutations confer upon the cancer phenotype should assist with prioritization of future precision-targeted therapies [3335], as well as identify rare substitutions that are significant drivers of tumorigenesis and tumor maintenance.…”
Section: Introductionmentioning
confidence: 99%
“…Mutations are acquired in response to various environmental stressors causing random DNA replication and DNA repair errors [28], thereby leading to the development of disease subtypes by clonal expansion of cells with a survival advantage [29]. HNSCC patients of different race showed a distinct mutation spectrum [22]. These gene mutations along with HPV infection are established to further contribute to inter-and intra-tumoral heterogeneity [18,[20][21][22][23].…”
Section: African American With Hnscc Tumors Harbor Higher Somatic Mutation Frequency Than Whitesmentioning
confidence: 99%
“…Evidence from clinical trials suggested that the response to immunotherapy in HNSCC [16,17] depends on availability of neo-antigens and a local immunosuppressive tumor microenvironment. While multiple studies have reported the influence of genetic changes, epigenetic modifications and mutations in specific protein domains [18][19][20][21][22][23] in HNSCC disparity, the influence of a global somatic mutational signature on the intricate association between immune response and metabolic alterations is still elusive. Hence, the current study aims to comprehensively investigate the key genetic and epigenetic variations that drive the differential immune phenotype among AA and Whites with a predicted contribution to intratumoral metabolic milieu, resulting in disparate patient outcome.…”
Section: Introductionmentioning
confidence: 99%
“…With personalized medicine on the horizon, it is also important to realize that racial disparities may extend to the realm of molecular medicine as well. Racial differences in the prevalence of specific head and neck cancer mutations, for example, have been found . As our field's understanding of cancer genetics grows, the importance of including racial and ethnic minorities in research efforts becomes even more critical–ensuring that the genetic diversity of the highest risk groups is included in major genetic studies and clinical trials.…”
Section: Introductionmentioning
confidence: 99%